DasR positively controls monensin production at two-level regulation in Streptomyces cinnamonensis. (1st December 2016) - Zhang, Yue; Lin, Chun-Yan; Li, Xiao-Mei; Tang, Zheng-Kun; Qiao, Jianjun; Zhao, Guang-Rong
Abstract: The polyether ionophore antibiotic monensin is produced by Streptomyces cinnamonensis and is used as a coccidiostat for chickens and growth-promoting agent for cattle. Monensin biosynthetic gene cluster has been cloned and partially characterized. The GntR-family transcription factor DasR regulates antibiotic production and morphological development in Streptomyces coelicolor and Saccharopolyspora erythraea . In this study, we identified and characterized the two-level regulatory cascade of DasR to monensin production in S. cinnamonensis . Forward and reverse genetics by overexpression and antisense RNA silence of dasR revealed that DasR positively controls monensin production under nutrient-rich condition. Electrophoresis mobility shift assay (EMSA) showed that DasR protein specifically binds to the promoter regions of both pathway-specific regulatory gene monRII and biosynthetic genes monAIX, monE and monT . Semi-quantitative RT-PCR further confirmed that DasR upregulates the transcriptional levels of these genes during monensin fermentation. Subsequently, co-overexpressed dasR with pathway-specific regulatory genes monRI, monRII or monH greatly improved monensin production.